PENGARUH KAPSUL EKSTRAK DAUN KELOR (Moringa Oleifera) TERHADAP KECUKUPAN ASI PADA IBU MENYUSUI - Bunga Tiara Carolin; Cholisah Suralaga; Gita Dharmawanti (LPPM Universitas Abdurrab, 2022)
Exclusive breastfeeding durinthe first 6 months of infants is very important, especially in the early period of life, this is because it can affect the health of the baby. Efforts to overcome this include improving the quality of breast milk, one of which is consuming Moringa leaf extract capsules because of the phytosterols that can increase milk production. The purpose of the study was to determine the effect of Moringa leaf extract capsules on breast milk production in breastfeeding women in the Cileles Health Center Lebak Banten. This study was a quasi-experimental research design with one group pretest-posttest design. The sample in this study wes mothers and babies who breastfeeding in the Cileles Health Center which consists 15 respondents with purposive sampling technique. The research instrument used a questionnaire. Analyzed using paired sample t-test. The results of univariate analysis of breast milk production in breastfeeding women before being given Moringa leaf extract obtained an average value = 5.40, the average post-test value was 7.47 so that the difference in the average value was 2.07. The results of the bivariate paired sample t-test have an effect with a significant value of 0.000. Conclusions and Suggestions: Moringa leaf extract capsules have an effect on breast milk production. It is hoped that midwives can apply it to breastfeeding women in the process of increasing breast milk production, one of which is by consuming extra Moringa leaf capsules or consuming vegetables and Moringa so that milk production increases.